การรับรองสิทธิเสรีภาพของชนชั้นในสังคมไทยในสมัยรัตนโกสินทร์ (รัชกาลที่ 4-รัชกาลที่ 7) - อธิลักษณ์ ศรีหทัย (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To study at the sources and recognition of rights and liberty during the reign of King Rama IV to King Rama VII that is ruled under absolute monarchy administration. Social state in that time being under class system which obviously class division, occurring in the law that provide recognition of rights and liberty of class according to status where the class be. The aforesaid reign mentioned above had been provided development of law concerning the recognition of rights and liberty which relieved intense compulsory of law in that period. It also made the law hereof relieving from intense state between class in social too. Results getting from studying found that was propagation of comceptual law concerning rights and liberty to people in every in classes on that time in Thailand by promulgation laws in government gazette. It also had many consequences in law aspect. However, characteristic of the recognition occurring that time is enough and respond to a requiring of people in each reign at least in satisfied level. The every King s idea showing foundation and attempt for providing liberty to people in order to develop the administrative of this country for democratic adminstration afterward. Nowadays, the important elements that set up the means of recognition of rights and liberty will shift upon the attitude of governor that is not differ from the reign of absolute monarchy administration. If governor has concept to protect status of people and people also try to study and understans with the provision of law regarding the recognition of rights and liberty, it can develop and respond to the requiring of people in efficient manner.